The dynamics of the cognitive functions of athletes at various stages of competitive activity - Olena Gant; Iaroslava Malyk (Kharkiv State Academy of Physical Culture, 2019)
Purpose: to study the performance characteristics of the cognitive functions of athletes at various stages of competitive activity. Material and methods: analysis of scientific and methodological literature, the Schulte Tables technique, the Mini Mental Status Exam technique, the 10 Words Memorization technique. The study involved 99 highly qualified athletes aged 18 to 23 years. The first stage of the study took place in the conditions of competitive activity, the second stage - in the post-competition period. Statistical processing of the obtained empirical data was carried out using the method of establishing the probability of deviations (by t-Student criterion). Results: a psychodiagnostic survey of the performance of cognitive functions of athletes aged 18 to 23 years was conducted. The features of the attention functions and mnestic functions of athletes in the conditions of competitive and post-competitive activity are determined. Conclusions: it is shown that the structure of cognitive dysfunctions during the period of extreme competitive activity is determined by a decrease in the volume of immediate and longterm memory, a decrease in the productivity of the memorization process, defects in selectivity, a decrease in the volume of voluntary attention, a violation of the processes of concentration, distribution, and switching. It has been established that the decrease in the cognitive performance of athletes in extreme conditions of competitive activity is functional and can be reduced in the first decade of the post-competition period.